George W. Bush's healthy forests : reframing the environmental debate - Switzer, Jacqueline Vaughn (University Press of Colorado, 2005)
The authors detail Bush administration reframing of America's environmental debate, identifying players, events, and strategies that expedited a policy shift that impacts public lands and long-standing avenues of public involvement.
Keywords: Forest policy -- United States.; Forest management -- United States.; Forest management -- Environmental aspects -- United States.; Politique forestière -- États-Unis.; Forêts -- Gestion -- États-Unis.; Forêts -- Gestion -- Aspect de l'environnement -- États-Unis.; NATURE -- Natural Resources.; BUSINESS & ECONOMICS -- Environmental Economics.; BUSINESS & ECONOMICS -- Green Business.; NATURE -- Environmental Conservation & Protection.; Forest management; Forest management -- Environmental aspects; Forest policy; United States